Studi Reduksi Beban Termal ke Dalam Ruangan Secara Konveksi dengan Sistem Underground Thermal Storage Sebagai Altenatif untuk Mendinginkan Ruangan Rumah Hunian - Indra Mamad Gandidi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2011)
Space cooling is required all year around in the tropics area especially Indonesia. To provide the space cooling requirement, the electricity cost and environment impact are important aspect that it must be considered. The household in the tropical area is real conditions require a cooling device and greatest potential to use alternative cooling. In fact, solar radiation over the roof surface can be thrown to the environmental by convection mechanism in order to the room can be remaining in comfortable condition.The experimental investigation was performed to two model of household. That is household without and using evaporator, respectively. Also in this reasearch, evaporator was placed in two location, over and or under surface of the roof. Water from underground thermal storage is used as a working fluid to pick up amount of heat over the roof and then rejected on thermal storage environment. The mesurement of experimental data was conducted start from 08.00 WIB to 17.00 WIB. Roof temperature will fluctuation with raise of time start from the morning to evening. The maximum temperature difference between household without and with evaporator are ± 12 0C with water mass flow rate 0.0125 kg/s and ± 8 0C with water mass flow rate 0.0187 kg/s for evaporator over and under the surface of the roof respectively.This research result have still uncomfortable condition for household. However, this research can be used as an initial step to build up a cooling system with low cost of electrical power and environmental friendly. Moreover, thermal reduction on the wall and the window to increase in the performance of this method are necessary. Then, the impromevent of roof geometry has to performed to keep the maximum interface area of heat transfer. Keywords: convection mechanism, space cooling, household